PENGEMBANGAN DAN MODIFIKASI ESTETIK DALAM PEMBUATAN CROWN DAN BRIDGE - Thambas A., Andhi Kartini; Dewi, Ratna Sari (MAJALAH ILMIAH WIDYA, 2012)
Aesthetic Dentistry is improving in line with the shift in demand of dental care that is more focused of crown and bridge, thereare several factors to be considered. Harmony between the denture with natural teeth be a mayor factor in preserving the heath ofthe surrounding tissue. The factors that should be considered in the treatment of crown and bridge are smile analysis, dentofacialorientation, horizontal perspective, shape, color, and position of teeth, materials to be used, as well as the manufacturing process.Determination of the proper design and consideration of the above factors is the key to success in the treatment of crown and bridge